2022
DOI: 10.3389/fpsyg.2022.896156
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Workplace Violence Against Healthcare Workers During the COVID-19 Pandemic: A Systematic Review and Meta-Analysis

Abstract: BackgroundA large number of anxious and concerned people refer to health centers during the COVID-19 pandemic, increasing the workload of healthcare workers (HCWs) and violence against these professionals. The present study aimed to estimate the prevalence of workplace violence (WPV) against HCWs during the COVID-19 pandemic.MethodsThis systematic review and meta-analysis was conducted via searching in databases such as Scopus, PubMed, and Web of Science, and observational articles reporting the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 39 publications
(29 reference statements)
3
46
0
1
Order By: Relevance
“…Violence against healthcare workers has become an international emergency, destroying the foundation of the health system and seriously affecting the health of patients ( 32 ). In our study, the incidence of WPV experienced and witnessed by healthcare workers, which was in the range from 50.0 to 84.2% reported in the past ( 33 , 34 ), similar to the prevalence of other outcomes during the COVID-19 pandemic, such as the combined prevalence of WPV among healthcare workers in Asia and the America at 44.0 and 58.0%, respectively ( 35 ). But lacking the comparable studies a year or more after the peak of COVID-19.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Violence against healthcare workers has become an international emergency, destroying the foundation of the health system and seriously affecting the health of patients ( 32 ). In our study, the incidence of WPV experienced and witnessed by healthcare workers, which was in the range from 50.0 to 84.2% reported in the past ( 33 , 34 ), similar to the prevalence of other outcomes during the COVID-19 pandemic, such as the combined prevalence of WPV among healthcare workers in Asia and the America at 44.0 and 58.0%, respectively ( 35 ). But lacking the comparable studies a year or more after the peak of COVID-19.…”
Section: Discussionsupporting
confidence: 77%
“…There is insufficient research on the relationship between the mental health status of health workers and WPV during the COVID-19 outbreak, especially on the long-term impact of 1 year or more after the peak of COVID-19. Several studies have previously reported on the psychological outcomes of healthcare workers during the COVID-19 pandemic ( 53 , 58 ), and some studies have reported WPV against healthcare workers during the COVID-19 pandemic ( 35 ), but studies on the relationship between the two outcomes are lacking, especially in different times of COVID-19. We hypothesized that the mental health status of health workers and WPV were interactive.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread COVID-19 pandemic has resulted in an increase in acts of violence and bullying directed towards healthcare workers (HCWs) [ 25 , 26 ]. During the COVID-19 outbreak, there had been several reports of acts of violence, harassment, and stigmatization directed toward HCWs as well as patients [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ramzi ZS et al in their recent systematic review and meta‐analysis, concluded violence against HCWs to have risen during the pandemic, with the prevalence estimated to be 47% ranging from verbal to physical violence 19 . The study included 17,201 medical staff and the prevalence of workplace violence statistics was irrespective of sample sizes and the age of HCWs 19 . The International Committee of Red Cross (ICRC) reported total 611 cases where HCWs faced violence, harassment and stigmatization including 20% being physical assault, 15% being discriminatory violence and 15% being verbal abuse 17 .…”
Section: Resultsmentioning
confidence: 99%